2013
DOI: 10.1108/intr-06-2012-0114
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the predictive power of social media

Abstract: During the past years he has initiated and managed several research projects (e.g., IST EURO-CITI, IST eGOV, eContent eMate). He has also participated in numerous research projects (FP6/IST, e.g., OneStopGov, DEMO-net, FP5/IST, TAP, ACTS, ESPRIT, SPRITE-S2, etc.), service contracts (e.g. MODINIS Interoperability Study, European eParticipation Study) and standardisation activities (CEN/ISSS project on eGovernment metadata, CEN/ISSS eGovernment Focus Group). He has more than 120 publications in eGovernment, ePar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
108
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 60 publications
1
108
0
5
Order By: Relevance
“…Females have significantly higher frequency of "likes," comments and messages on Facebook than males do. The results verified that women have higher participation rates, higher frequency of posting and commenting to their friends 2,28,45 . This higher involvement made social support easier to exchange.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Females have significantly higher frequency of "likes," comments and messages on Facebook than males do. The results verified that women have higher participation rates, higher frequency of posting and commenting to their friends 2,28,45 . This higher involvement made social support easier to exchange.…”
Section: Discussionsupporting
confidence: 65%
“…Social network sites (SNSs) are changing the behavior of Internet users 1,2 . The appearance of SNSs has changed the form of information from centralization and broadcasting into collaboration and sharing 3 .…”
Section: Introductionmentioning
confidence: 99%
“…At the time of searching, Academic Search Premier permitted export of 100 citations per batch and Web of Science permitted export of 500 citations per batch. All citations from each round of searches were exported in batches until all of the results were copied into EndNote online.Google Scholar was included as one of the databases searched for during this literature review due to its broad reach across interdisciplinary academic scholarship indexed on the Internet and its use in prior literature review studies (see Błachnio et al, 2013;Dhir et al, 2013;Kalampokis et al, 2013;Williams et al, 2013;Wilson et al, 2012). Unfortunately, Google Scholar has certain limitations.…”
mentioning
confidence: 99%
“…Some authors have focused on categorization of trends in academic literature related to specific social media platforms such as Facebook (Błachnio, Przepiórka, & Rudnicka, 2013;Caers et al, 2013;Hew, 2011;Manca & Ranieri, 2013;Nadkarni & Hofmann, 2012;Wilson, Gosling, & Graham, 2012), Twitter (Dhir, Buragga, & Boreqqah, 2013;Williams, Terras, & Warwick, 2013), or YouTube (Snelson, 2011). Other studies are grounded within a particular subject or field of study to examine social media as it relates to topics such as adolescent well-being (Best, Manktelow, & Taylor, 2014), health-care professionals (Hamm et al, 2013), type 1 diabetes (Jones, Sinclair, Holt, & Barnard, 2013), tourism and hospitality (Leung, Law, van Hoof, & Buhalis, 2013), or prediction of real-world events (Kalampokis, Tambouris, & Tarabanis, 2013).…”
mentioning
confidence: 99%
“…Social media data has been used as a primary source for the creation of predictive analytics models regarding various phenomena such as elections, stock market and product sales. An analysis of 52 relevant empirical studies concluded that social media data should go through a data conditioning process, which is similar to the one that we have presented in the proposed linked open government data analytics approach [19]. The same study revealed that this kind of open data could be successfully used for the development of predictive models in various problem areas.…”
Section: Related Workmentioning
confidence: 76%